Aeroelastic tailoring method of tow-steered composite wing using matrix perturbation theory. (15th February 2020) - Zhang, Bing; Chen, Kanglong; Zu, Lei
Abstract: In this study, a computational method based on matrix perturbation theory was proposed to solve the aeroelastic sensitivity of the fibre angle of tow-steered composite wings and find the optimal local fibre paving path for aeroelastic tailoring. Firstly, the finite element model of straight fibre composite wing was created with the multilayer composite shell element in MSC/NASTRAN. Then, the flutter velocity-sensitive region with local fibre angle was determined using matrix perturbation theory. The fibre angles were carefully adjusted only in the highly sensitive region to increase the flutter velocity, and the optimal fibre paving path was obtained. Genetic algorithm based on traditional aeroelastic tailoring method was used to carry out aeroelastic tailoring for the wings of straight and curved fibre laminated plates. Calculation results of the two tailoring methods indicate that the proposed method only needs to optimise the fibre angle in a small region to achieve the same aeroelastic tailoring effect of the traditional optimisation algorithm for tow-steered composites. The obtained maximum curvature of the fibre is also greatly decreased, which effectively reduces the difficulty in the paving process of the curvilinear fibre. The designability of tow-steered composite wings can be further improved.